PERANCANGAN SISTEM INFORMASI PENDAFTARAN PENERIMAAN SISWA BARU BERBASIS WEB PADA SDN PASIRDURUNG 1 PANDEGLANG - Rustam Effendi; Hamid Al Jufri; Iqbal Fernando; Asep Sapaatullah; Rahadian Arief; Elsa Lestari (Jurnal Ilmiah Sistem Informasi, 2022)
The information system has a very large impact, one of which concerns the registration process for new student admissions at Sdn Pasirdurung 1 Pandeglang. Sdn Pasirdurung 1 Pandeglang is an educational institution that is useful for screening prospective students who are selected according to the criteria determined by the school to become their students. Registration of prospective new students at Sdn Pairdurung 1 Pandeglang is still done manually with a recording system in the registration book. In managing data on the acceptance of new prospective students, they still use a record system in the registration ledger which results in data loss and is prone to fraudulent practices in the implementation of student registration. The system analysis method in this study uses PIECES analysis. The system design method in this study uses the Waterfall model while the data collection techniques used in this study are interviews, observations and literature studies. The results of the research on the new student registration information system include inputting prospective new student data, printing registration forms and printing prospective student data reports on the system. By using a computerized system, it is hoped that it will make it easier for users to manage new student admissions data, starting from data input, selection and report generation